PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI INTERNAL DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN DI DINKES KABUPATEN BLITAR - Reti Nurhabibah; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2020)
The istudy iaimed iwas ito idetermine ithe ieffect iof ipartially ior isimultaneously itransformational ileadership, iinternal icommunication iand iorganizational iculture ion iemployee ijob isatisfaction iin ithe iHealth iOffice iof iBlitar iDistrict. iThis iresearch iis iquantitative iresearch imethods iusing imultiple ilinear iregression idata ianalysis itechniques. iThe iresults iof ithe istudy ithat ithere iis ian iImpact iof itransformational leadership, internal communication and organizational culture simultanly on job satisfaction in the Health Office of Blitar District. Impact iof itransformational ileadership ion ijob isatisfaction iin iHealth iOffice iof iBlitar iDistrict. iImpact iof iinternal icommunication ion ijob isatisfaction iin iHealth iOffice iof iBlitar iDistrict. iImpact iof iorganizational iculture ion ijob isatisfaction iin ithe iHealth iOffice iof iBlitar iDistrict.